Hamka’s tasauf modern: an outlook on happiness - Rahman, Azizah; Muhamad Shukri, Abdul Salam (IIUM Press, 2018)
Introduction Hamka (1908-1981)’s Tasauf Modern (Modern Sufism) first published in August 1939 was a compilation of an earlier year and a half series of articles on ‘happiness’ from the weekly columns of the magazine Pedoman Masjarakat (Guidance for Society) where he was its chief-editor. The first article which appeared through the magazine’s circulation, dated 21st April, 1937, came with the reminder from the author, that he was writing in response to the requests of the magazines’ faithful followers, especially the elderly who had gone through so much of life’s hardships (pahitgetir).1